The ceramic trade between China and Southeast Asia during the Song Dynasty (960-1279) - Li, P (2020)
This thesis studies the shipwrecks in the South China Sea and their recovered artefacts to discuss the ceramic trade between South China and Southeast Asia during the Song dynasty (960-1279). This period is of particular interest because it was when Chinese ceramics started to be exported in bulk and make its name around the world. And shipwrecks in the South China Sea are the best materials to uncover the first leg of the long-distance trans-Asian trade route that led from China to the Mediterranean. Although there have been cases studies regarding one or several shipwrecks, thorough research that examines the overall findings of this period and addresses not only the products but also the trade network and the market of the products is somewhat lacking. To this aim, this thesis attempts to address the central questions as to how the trade was conducted and by whom, what are the changes of the exported ceramic types during this period and why, and whether there were vessel forms and decoration made to cater to the need of the Southeast Asian market. In doing so, the thesis provides a broader picture of the ceramic trade during the Song period and manages to extract some information on the human level.